PENGARUH LINGKUNGAN KERJA, KOMPETENSI, DAN NILAI PRIBADI TERHADAP KINERJA PEGAWAI PADA BIDANG PROFESI DAN PENGAMANAN POLDA SUMUT - Eni, Eni; Utama, Indra; Wulandari, Sari; Tumanggor, Mutawaqil Bilah (Universitas Dharmawangsa, 2024)
This study aims to determine the influence of work environment, competence, and personal values on employee performance in the Profession and Security Division of the North Sumatra Regional Police. This type of research is associative research with a quantitative approach. The sample in this study amounted to 109 employees of the North Sumatra Regional Police BIDPROPAM. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the work environment has a positive and significant effect on employee performance at the North Sumatra Regional Police BIDPROPAM. This is concluded based on the results of the partial significance test (t-test) with a t-count value of 3.393> t table 1.659 with a significance level of 0.00 <0.05. 2. Competence has a positive and significant effect on employee performance at the North Sumatra Regional Police BIDPROPAM. This is concluded based on the results of the partial significance test (t-test) with a t-count value of 4.696> t table 1.659 with a significance level of 0.00 <0.05. 3. Personal values have a positive and significant effect on employee performance at BIDPROPAM Polda Sumut. This is concluded based on the results of the partial significance test (t-test) with a calculated t value of 5.272> t table 1.659 with a significance level of 0.00 <0.05. 4. Work environment, competence, and personal values have a positive and significant effect on employee performance at BIDPROPAM Polda Sumut. This is concluded based on the results of the simultaneous significance test (F-test) with a calculated F value of 18.02> F table 2.46 with a significance level of 0.00 <0.05.